Persepsi dan Status Kesehatan Mental Penderita Diabetes Melitus Tipe II Suku Dayak - Asi, Feronika Adithia Eka; Saragih, Rosiana Evarayanti; Ranimpi, Yulius Yusak (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Diabates Mellitus (DM) type II, a long-term metabolic disorder caused by high blood sugar, is one of the major health problems in the world. Central Kalimantan Province, Palangkaraya City has 3,885 cases of DM in 2012. Prevalance of DM type II patients in the Regional Public Hospital of Doris Sylvanus Palangka Raya increases from 375 cases (in 2007) to 514 cases (in 2009). DM can affect the patients physically and psychologically. Patients will respond differently to illness, influenced by previous experience and social culture. Dayak people are ethnic majority in Central Kalimantan. Study aims to describe the perception of health and mental health status of patients with type II DM in cultural context of Central Kalimantan. Method: This research was conducted using qualitative descriptive method. Data collected through in-depth interview from 10 participants. Data was analyzed with Miles and Huberman models using data reduction, data display, and conclusion drawing and verification. Results: Health perception and mental health status of people with type II DM in the cultural context of Central Kalimantan influenced by health and illness perception, emotional self-control, and thinking capability. Conculsion: Health perceived as conditions when the body capable enough to perform daily activities, in other hand illness perceived as conditions of the body unable to perform daily activities. These understanding related to participantsâ experience and local culture. Paticipantsâs thinking capability decrease such as difficulty remembering due to aging and DM type II. They have positive perspective toward life after getting type II DM that affected their emotional self-control.